Sistem Informasi Pariwisata Kabupaten Agam Sumatera Barat Berbasis Webgis - Dwi Marsiska Driptufany; Ahmad fikri; Fajrin Fajrin; Defwaldi Defwaldi; Ilham Armi (Jurnal Sains dan Ilmu Terapan, 2025)
Tourism is a strategic sector in regional development. Agam Regency offers a variety of tourism potential, including natural, cultural, religious, and artificial attractions. However, information about these attractions is still fragmented and unintegrated. This study aims to identify the distribution of tourist attractions and design a WebGIS-based tourism information system. Primary data were collected through field observation and documentation, while secondary data were obtained from government agencies. Spatial data were processed using QGIS and ArcGIS, non-spatial data were stored in MySQL, and the system was developed using HTML, CSS, JavaScript, PHP, and XAMPP. The results indicate that the system successfully displays interactive maps, provides detailed descriptive information, and is compatible across devices. The user feedback has been positive, indicating high satisfaction with the system. This WebGIS-based system proves to be an effective tool for tourism promotion and management, helping Agam Regency integrate its tourism potential and make it more accessible to tourists and stakeholders alike.